2000
DOI: 10.1093/nar/28.17.3316
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the structural and functional diversity of RNA: analog uridine triphosphates as candidates for in vitro selection of nucleic acids

Abstract: Two analog uridine triphosphates tethering additional functionality, one a primary amino group and the second a mercapto group, were prepared and tested for their compatibility with in vitro RNA selection procedures. 5-(3-Aminopropyl)uridine triphosphate (UNH 2 ) as a uridine substitute was a more effective substrate for T7 RNA polymerase than 5-(2-mercaptoethyl)uridine triphosphate (USH). However, both functioned in transcription assays of 100 nt templates to generate RNA transcripts in quantities sufficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 31 publications
(36 reference statements)
0
31
0
2
Order By: Relevance
“…Taq DNA polymerase, RNase T1, T4 PNK, and calf intestinal alkaline phosphatase were purchased from Boeringer (Mannheim, Germany). The common nucleotide triphosphates were purchased from Pharmacia (Piscataway, NJ) and the 5-(3-aminopropyl)uridine triphosphate (UNH 2 ) was prepared as reported (30). The TA cloning kit was purchased from Invitrogen (Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taq DNA polymerase, RNase T1, T4 PNK, and calf intestinal alkaline phosphatase were purchased from Boeringer (Mannheim, Germany). The common nucleotide triphosphates were purchased from Pharmacia (Piscataway, NJ) and the 5-(3-aminopropyl)uridine triphosphate (UNH 2 ) was prepared as reported (30). The TA cloning kit was purchased from Invitrogen (Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro selection is a combinatorial technique that generates receptors, ligands, and catalysts from nucleic acid libraries containing as many as 10 14 -10 16 different molecules and is a powerful method to explore the sequence space of biopolymers in search of functional domains. Some effort has been devoted to developing in vitro selection processes that use modified monomer triphosphates as substrates for polymerases (27)(28)(29)(30)(31)(32)(33)(34)(35)(36), and several in vitro selection experiments have been undertaken to select for catalysts or aptamers whose functions depend on the presence of modified nucleotides (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48), with notable success (39,40,(43)(44)(45)(46)(47). On the other hand, modified building blocks have not proven to always be critical in obtaining superior receptors or catalysts (40,42,48,49).…”
mentioning
confidence: 99%
“…These proved to be substrates for T7 RNA polymerase in transcription of a 93 nt DNA template. Vaish et al have reported transcription of a 100 nt DNA template using the two C5-substituted UTP derivatives shown in Scheme 10.12 [46]. Although transcription was less efficient than with UTP, full-length transcripts were obtained.…”
Section: Incorporation Of Diverse Functionality Into Dnamentioning
confidence: 99%
“…Die effiziente Laborsynthese sequenzdefinierter synthetischer Heteropolymere etwa gleicher Länge wie funktionelle Proteine und Nucleinsäuren bleibt eine enorme Herausforderung. DNA-Polymerasen, [128][129][130][131][132][133] RNA-Polymerasen [134][135][136][137] und Ribosomen [138][139][140][141][142] sind bekannt für ihre [1,85,92,[144][145][146][147][148][149][150] zeigten, dass mit Monomeren mit aktivierten Phosphaten eine geringe Zahl an DNA-, RNA-, PNA-, HNA-oder ANA-gestützten Phosphoveresterungen zwischen Mono-, Di-, Tri-oder Oligonucleotiden gelang, wobei oligomere DNA-oder RNA-Produkte mit mäßiger Effizienz (üblicherweise < 50 % Ausbeute pro Monomerkupplung) erhalten wurden.…”
Section: Dna-gestützte Polymerisationunclassified